Characterizing the Evolution of Trapped scCO2 Curvature in Bentheimer and Nugget Sandstone Pore Geometry. (6th March 2020) - Dalton, Laura E.; Crandall, Dustin; Goodman, Angela
Abstract : During a Geologic Carbon Storage process, supercritical CO2 (scCO2 ) is subjected to a series of dynamic and static conditions where the relationship between pore geometry and the trapped scCO2 curvature remains to be established. To mimic the dynamic process, two sandstones, Bentheimer and Nugget, were subjected to two successive drainage and imbibition (D-I) cycles and X-ray computed tomography scanned at each residual state to capture the wettability evolution at static conditions in the same pore geometry. Both sandstones contain similar grain size distributions, pore size distributions, and pore interconnectivity but differ in that the Nugget formation contains approximately half the porosity of the Bentheimer sandstone, and the pore network contains dead-end pores. scCO2 size distributions, strain calculations, and geometric contact angle measurements were used to characterize the curvature of scCO2 in different pore types between cycles. An increase in geometric contact angle was the greatest when advancement along the pore network of the same ganglion occurred between cycles while strain increased the most with pore-filling trapping. Moreover, Nugget sandstone results in a greater aggregated residual saturation and shows a clear increase in scCO2 sizes with an additional D-I cycle while scCO2 in the Bentheimer core shows a more complex response with some ganglion increasing and some decreasing in size with an additional D-I cycle. From this work, we suspect the pore geometry is playing a role in scCO2 size distributions and use this information to suggest using water pulses to enhance trapping capacity in lower porosity sandstones.